Analysis of the characteristics of blood inflammatory cytokines and their influencing factors in acute exacerbations of allergic asthma in children - Shen, Ren; Yang, Shanpu; Zhou, Yan; Li, Jinɡjinɡ (Frontiers in Pediatrics, 2025)
BackgroundExploring the characteristics of serum inflammatory cytokine changes during acute exacerbations of pediatric allergic asthma, and analyzing factors influencing poor asthma control and predictive indicators.MethodsForty children with acute exacerbations of allergic asthma, either outpatients or inpatients, were selected as the observation group, and 40 healthy children undergoing physical examinations during the same period served as the control group. Flow cytometry was used to analyze the characteristics of blood inflammatory cytokines in both groups. Logistic multiple regression was used to analyze the influencing factors of poor asthma control, and ROC curve analysis was used to evaluate the indicators for predicting poor asthma control.ResultsThere were statistically significant differences in the levels of IL-2, IL-4, IL-10, IL-13,IFN-γ, TNF-α, as well as the ratios of IL-2/IL-4, IL-2/IL-5, IL-2/IL-10, IL-2/IL-13, IFN-γ/IL-4, IFN-γ/IL-5, IFN-γ/IL-13, TNF-α/IL-4, TNF-α/IL-5, TNF-α/IL-6, TNF-α/IL-13 in the peripheral serum, and the expression of CD86, CD206, and CD86/CD206 in peripheral blood mononuclear cells (PBMCs) between the observation group and the control group (P < 0.05). Univariate analysis indicated that respiratory infections, exposure to allergens, irregular use of inhaled corticosteroids (ICS), and peripheral blood eosinophil counts may be associated with poor asthma control (P < 0.05). Receiving Subcutaneous Specific Allergen Immunotherapy (SCIT) may serve as a protective factor against poor asthma control (P < 0.05). Logistic multiple regression analysis showed that respiratory infections and irregular use of ICS were independent risk factors for poor asthma control (P < 0.05), while SCIT was an independent protective factor against poor asthma control (P < 0.05). ROC curve analysis shows that IL-13 has a high accuracy in predicting poor asthma control, with areas under the curve of 0.741.ConclusionsIn pediatric allergic asthma exacerbations, there is a decrease in the activity of Th1 cytokines and an increase in the activity of Th2 cytokines in the peripheral blood, accompanied by enhanced polarization of macrophages towards the M2 phenotype. Respiratory infections and irregular use of ICS are independent risk factors for poor asthma control, whereas SCIT is an independent protective factor against poor asthma control. IL-13 has high accuracy in predicting poor asthma control.